Biological Evaluation of Potent Triclosan‐Derived Inhibitors of the Enoyl–Acyl Carrier Protein Reductase InhA in Drug‐Sensitive and Drug‐Resistant Strains of Mycobacterium tuberculosis. Issue 11 (27th August 2014) - Stec, Jozef; Vilchèze, Catherine; Lun, Shichun; Perryman, Alexander L.; Wang, Xin; Freundlich, Joel S.; Bishai, William; Jacobs, William R.; Kozikowski, Alan P.
Abstract New triclosan (TRC) analogues were evaluated for their activity against the enoyl–acyl carrier protein reductase InhA in Mycobacterium tuberculosis (Mtb). TRC is a well‐known inhibitor of InhA, and specific modifications to its positions 5 and 4′ afforded 27 derivatives; of these compounds, seven derivatives showed improved potency over that of TRC. These analogues were active against both drug‐susceptible and drug‐resistant Mtb strains. The most active compound in this series, 4‐(n‐butyl)‐1, 2, 3‐triazolyl TRC derivative 3, had an MIC value of 0.6 μg mL−1 (1.5 μM) against wild‐type Mtb. At a concentration equal to its MIC, this compound inhibited purified InhA by 98 %, and showed an IC50 value of 90 nM. Compound 3 and the 5‐methylisoxazole‐modified TRC 14 were able to inhibit the biosynthesis of mycolic acids. Furthermore, mc24914, an Mtb strain overexpressing inhA, was found to be less susceptible to compounds 3 and 14, supporting the notion that InhA is the likely molecular target of the TRC derivatives presented herein.